'Doing the right thing': organizational effectiveness & phronesis in small tourism firms. Issue 13 (3rd July 2021) - Tomassini, Lucia
ABSTRACT: Drawing upon the Drucker's ([2006]. The effective executive . Harper Paperbacks.) definition of effectiveness as 'doing the right thing', this paper explores how small tourism firms driven by an ethical approach to tourism, here named as 'values-based', understand their organizational effectiveness. This study is guided by Aristotle's notion of phronesis (practical wisdom) aimed at developing and exercising an attitude towards 'good' actions. Using a narrative approach via unstructured interviews with owner-managers of small values-based Italian firms, these explorative research findings disclose an organizational effectiveness rooted in a personal intuitive disposition for 'doing the right thing', gained by practical first-hand experience, personal knowledge, and moral rectitude.